Innovative activity in the post- industrial economy and its stimulation by the mechanism of tax levers - Bandura, Zvenyslava; Holubetskyy, Pavlo (Herald of Economics, 2023)
Introduction. The current stage of economic development is characterized by qualitatively new requirements related to the peculiarities of being at the peak of the growth cycle of innovation and business activity. Globalization, informatization of production, the need to adapt to changes in the global economic situation, and the growing share and importance of intellectual and innovative industries are all characteristic of the post- industrial economy. A number of internal and external factors influence the development of innovation activity at both the macro and micro levels, one of which is the tax incentive mechanism.Purpose. The purpose of the article is to identify the main trends in the development of innovation activity in the world in general and in Ukraine in particular, and to provide a critical description of the methods of tax incentives as one of the most important factors of influence on such activity adopted in domestic and foreign fiscal systems.Methods. To achieve the goal set out in the study, the author uses general scientific methods: induction and deduction, analysis and synthesis, statistics, analogies (for studying the conceptual apparatus), and a dialectical approach to scientific knowledge of economic phenomena and processes, which made it possible to reveal the relationship between the development of innovation activity at the macro- and micro-level and global trends in the formation of new economic systems, the fiscal system of the State and the accounting and analytical system of an enterprise.Conclusions. The main global trends in the development of innovation activity are identified and the reasons for the decline in the innovation activity of domestic enterprises are disclosed. The mechanism of influence of fiscal policy on stimulation of innovation activity of enterprise is researched.Discussion are the need to study the most significant factors that influence the development of innovations and develop a mechanism for realizing their positive impact on the growth of innovation activity of an enterprise.